2017
DOI: 10.1007/s11356-017-0692-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of air pollution on spontaneous abortion, premature delivery, and stillbirth in Ahvaz, Iran: a time-series study

Abstract: Living in areas with high air pollution may have adverse effects on human health. There are few studies about the association between breathing polluted air and adverse pregnancy outcomes in the Middle East. The aim of this study was to determine the relationship between air pollution and spontaneous abortion, premature birth, and stillbirth in Ahvaz. A time-series study was conducted. Data about spontaneous abortion, premature deliveries, and stillbirth was collected from Ahvaz Imam Khomeini Hospital. Air pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 67 publications
3
49
0
Order By: Relevance
“…The World Health Organization estimates that air pollution is responsible for more than 1 million premature deaths each year across the world [7]. Recent studies conducted in relation to air pollution have shown that not only West ern Europe and North America but also developing coun tries are facing this health problem [8][9][10][11]. And it is pos sible that there is a relationship between chronic exposure to air pollution and coronary artery diseases [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The World Health Organization estimates that air pollution is responsible for more than 1 million premature deaths each year across the world [7]. Recent studies conducted in relation to air pollution have shown that not only West ern Europe and North America but also developing coun tries are facing this health problem [8][9][10][11]. And it is pos sible that there is a relationship between chronic exposure to air pollution and coronary artery diseases [12].…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter below 10 μm was the only type of par ticulate matter, which had been recorded at the air quality monitoring stations. There were 4 air quality monitoring stations in Ahvaz, including the environmental protection agency station (Mohit Zist), Naderi square station, Uni versity square station (Behdasht Ghadim), and the meteo rological organization station (Havashenasi) [8]. Accord ing to the environmental protection agency experts, the air quality monitoring station locations were representative of the ambient air quality of the whole city.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important causes of particulate matter air pollution in Ahvaz are its geographic location and topography, proximity to the Saudi desert, and emerging sources of dust in the neighboring countries. Other sources are transportation and existence of industries including oil, natural gas, and steel that have exposed this city to natural and man-made air pollution ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 Epidemiological evidence suggests that maternal exposure to ambient pollutants is associated with pregnancy loss. [5][6][7][8][9][10][11][12][13][14][15][16] With longterm exposure, even a weak effect of an environmental factor can result in a considerable disease burden. Quantifying the exposure-response function for maternal exposure to air pollution can provide new strategies to mitigate the risk of pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%